Women's Access to Islamic Higher Education - Nawangsari, Dyah; Elhady, Aminullah; Salam, Norodin (Jurnal Pendidikan Islam, 2020)
This study aims to describe women's access to PTKI (Perguruan Tinggi Keagamaan Islam/Islamic Higher Education) and ma'had aly institutions. The method used was a qualitative approach with a gender perspective. Interviews, observations, and documentary studies were applied to collect the data. This research was conducted in PTKI and ma'had aly institution that are located in East Java. The results show that there are gaps in accessing education between male and female students in the national context which can be seen from the net enrollment rate. This gap also occurred in women's educational participation at PTKI and ma'had aly institutions. The disparity of education access can be observed in terms of women's participation in intracurricular and extracurricular activities at ma’had aly institutions. There is a difference in the level of women's participation in Islamic higher education for Islamic studies compared to ma'had aly.